Formation of Intermetallics Layers in Ni-Ti System Prepared by Direct Energy Deposition - Salvetr, Pavel; Vavřík, Jaroslav; Školáková, Andrea; Novák, Pavel (Manufacturing Technology Journal, 2019)
The Ni-Ti alloys with approximately equiatomic chemical composition are one of the most important materials from the shape memory alloys. Excellent properties such as shape memory effect and superelasticity are based on the phase transformation between austenite and martensite structure of the NiTi phase. In the past the investigation of the preparation methods was focused on melting metallurgy - vacuum induction melting and arc re-melting and powder metallurgy routes like self-propagating high-temperature synthesis, hot isostatic pressing and spark plasma sintering. In the last several years importance of the additive manufacturing has increased significantly. This paper deals with formation of the Ni-Ti intermetallic phases between the nickel and titanium layers deposited on each other by direct energy deposition energy method. The varied mixture of the Ti 2Ni, NiTi and Ni3Ti phases was formed in agreement with the binary Ni-Ti phase diagram. Some problems like cracking and nickel loss have to be solved by preheating of platform or adjustment of laser parameters.
Keywords: Ni-Ti alloys; Additive manufacturing; Direct energy deposition